Legal Protection of Copyrighted Film Clips on The TikTok Platform - Arsya Yulhandi; Arief Budiono; Siska Diana Sari; Adetia Azmi Tanjung; Dang Panagaman Tamba; Nadia Bismi Hafifah; Dhia Asy Syafa (Universitas Muhammadiyah Surakarta, 2025)
The advancement of digital technology has significantly impacted copyright protection, particularly on social media platforms such as TikTok. This study aims to examine the effects of copyright infringement involving film excerpts on TikTok and to explore potential solutions for protecting such copyrighted content. The research employs a normative legal approach with doctrinal study, focusing on the analysis of relevant laws and legal literature. The findings indicate that uploading film excerpts without permission on TikTok violates Article 9(1) of the Copyright Law, resulting in both material and immaterial losses for copyright holders, while also shaping consumer habits toward illegal content access. Furthermore, effective copyright protection can be achieved through stricter law enforcement, increased public awareness, and the development of more advanced content detection systems on TikTok, modeled after YouTube's Content ID system.